Asparaginyl beta-hydroxylation of proteins containing ankyrin repeat domains influences their stability and function. - Hardy, A; Prokes, I; Kelly, L; Campbell, I; Schofield, C (2009)
Recent reports have provided evidence that the beta-hydroxylation of conserved asparaginyl residues in ankyrin repeat domain (ARD) proteins is a common posttranslational modification in animal cells. Here, nuclear magnetic resonance (NMR) and other biophysical techniques are used to study the effect of asparaginyl beta-hydroxylation on the structure and stability of 'consensus' ARD proteins. The NMR analyses support previous work suggesting that a single beta-hydroxylation of asparagine can stabilize the stereotypical ARD fold. A second asparaginyl beta-hydroxylation causes further stabilization. In combination with mutation studies, the biophysical analyses reveal that the stabilizing effect of beta-hydroxylation is, in part, mediated by a hydrogen bond between the asparaginyl beta-hydroxyl group and the side chain of a conserved aspartyl residue, two residues to the N-terminal side of the target asparagine. Removal of this hydrogen bond resulted in reduced stabilization by hydroxylation. Formation of the same hydrogen bond is also shown to be a factor in inhibiting binding of hydroxylated ARDs to factor-inhibiting hypoxia-inducible factor (FIH). The effects of hydroxylation appear to be predominantly localized to the target asparagine and proximal residues, at least in the consensus ARD protein. The results reveal that thermodynamic stability is a factor in determining whether a particular ARD protein is an FIH substrate; a consensus ARD protein with three ankyrin repeats is an FIH substrate, while more stable consensus ARD proteins, with four or five ankyrin repeats, are not. However, NMR studies reveal that the consensus protein with four ankyrin repeats is still able to bind to FIH, suggesting that FIH may interact in cells with natural ankyrin repeats without resulting hydroxylation. Overall, the work provides novel biophysical insights into the mechanism by which asparaginyl beta-hydroxylation stabilizes the ARD proteins and reduces their binding to FIH.